1989
DOI: 10.1192/bjp.154.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Family History and Cerebral Ventricular Enlargement in Schizophrenia

Abstract: Ventricular size was measured from CT scans in 48 patients meeting RDC for schizophrenia who had a first-degree relative with a history of treatment for major psychiatric disorder, in 48 age- and sex-matched schizophrenic patients with no such history in first- or second-degree relatives, and in 48 matched, healthy controls. There was no difference in ventricular size between those with and without a positive family history, although both groups showed ventricular enlargement with respect to normal controls. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Most studies have used operational diagnostic criteria to define the patient group, but have still differed widely in patients' demographic and treatment characteristics. There is now much evidence that these factors do influence the prevalence of abnormalities found (Luchins, 1982;Luchins & Meltzer, 1986;Owen & Lewis, 1986) and epidemiological samples such as first-episode patients (Turner et ai, 1986)or consecutive admissions from a defined catchment area (Iacono et ai, 1988) are to be preferred.…”
Section: Questions Of Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have used operational diagnostic criteria to define the patient group, but have still differed widely in patients' demographic and treatment characteristics. There is now much evidence that these factors do influence the prevalence of abnormalities found (Luchins, 1982;Luchins & Meltzer, 1986;Owen & Lewis, 1986) and epidemiological samples such as first-episode patients (Turner et ai, 1986)or consecutive admissions from a defined catchment area (Iacono et ai, 1988) are to be preferred.…”
Section: Questions Of Methodologymentioning
confidence: 99%
“…This is despite the low rates of obstetric complications in samples examined, which increases the likelihood of a type 2 error. A positive correlation has been reported between obstetric complications and ventricular size (Turner et al, 1986;Pearlson et al, 1989), frontal-horn area (DeLisi et al, 1986)and combinations of ventricular enlargement with sulcal (Owen et al, 1988) or thirdventricle widening (Cannon et al, 1989). Five studies have shown no such correlation (Reveley et ai, 1984;Pearlson et al, 1985;Nimgaonkar et al, 1988;Johnstone et al, 1989;Kaiya et al, 1989).…”
Section: The Natural History and Aetiology Of Ct Abnormalitiesmentioning
confidence: 99%
“…Of the studies looking for an association between family history and ventricle size, five have reported an inverse correlation between ventricular size and positive family history (Reveley et al 1984;Cazullo et al 1985;Turner et al 1986;Romani, 1987;Owen et al 1989). One study found a positive correlation (Nasrallah et al 1983) and one evidence of a curvilinear correlation (Owens et al 1985).…”
Section: Correlates Of Ventricle Sizementioning
confidence: 99%
“…These patients are also less likely to show ventricular enlargement on CT scan (Owen et al 1989). The most parsimonious explanation for this, and for the better outcome in women, is that many cases of so-called later-onset schizophrenia in women have more in common, aetiologically, with affective psychosis than schizophrenia.…”
Section: Female Preponderance In Later Onset Schizophreniamentioning
confidence: 99%